Evaluation of the Inhibitory Effectiveness of Some Common Honeys in Libya against the Growth of Pathogenic Bacteria. - Altounsi, Ritaj Mohamed; Ali, Hasan Mohamed; Sharaf, Aya Khalil (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
The use of natural products has become a common method in treating diseases due to their antioxidant and antibacterial compounds. Honey is an example of this. Honey is a natural product with a sweet taste, saturated with sugars, produced by bees from different plant sources, and has an effective effect in resisting and eliminating bacteria. Therefore, this study aimed to evaluate the inhibitory effectiveness of some honey samples collected from different regions of Libya, and compare their effect with antibiotics. The antimicrobial potential of different types of honey was tested against pathogenic bacterial strains using the agar diffusion method. The results showed that Sidr honey and a mixture of Sidr and spring honey showed the highest antibacterial activity against Gram-positive bacteria S. aureus, followed by Spring honey, which showed an inhibitory effect against Gram-negative bacteria K. pneumoniae, while other types of honey showed varying results against bacteria that vary according to the type and concentration of honey. Therefore, this study indicated that honey may be used as a natural product as an alternative to antibiotics.
Keywords: Honey; Honey concentration; Inhibitory effect of honey; Pathogenic bacteria; Antibiotic